ECHNOLOGICAL CULTURE IN IMPROVING THE PERFORMANCE OF INFORMATION SPECIALISTS IN UNIVERSITY LIBRARIES: A FIELD STUDY AT THE CENTRAL LIBRARY OF MOHAMED BOUDIAF UNIVERSITY - M'SILA – - RADJAI Smail & FATHI Abbes (Ziglôbitha)
Abstract: This study aimed to explore the role of technological culture in improving the job performance of information specialists at the central library of M'sila University. A comprehensive survey methodology was employed, and the study reached several findings, the most significant of which were: information specialists at the central library possess a technological culture that qualifies them to enhance their job performance. Moreover, the use of modern technology in the library leads to providing library services that align with the needs of beneficiaries.